2011
DOI: 10.1155/2011/452328
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and spectroscopic study on the binding of interaction anionic phthalocyanine with calf thymus DNA

Abstract: Abstract.The interaction between anionic form of copper (II) N,N ,N ,N -tetrasulfonated phthalocyanine Cu (tspc) and to calf thymus deoxyribonucleic acid (ct-DNA) is investigated by measuring UV-vis absorption and fluorescence spectroscopy in phosphate buffer. The binding constant and stoichiometry were determined by analysis of optical absorption spectra of phthalocyanine at various ct-DNA concentrations using SQUAD software. The static mode of fluorescence quenching of phthalocyanine by calf thymus deoxyribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The stability of the bound complex is determined by the differences in the noncovalent interactions between the Pc and the DNA as temperatures varied using a nonlinear least-squares algorithm. 48 At these temperatures, DNA does not undergo any structural degradation. The absorption spectra were analyzed by assuming phthalocyanine:DNA molar ratios as 1:1 and 2:1.…”
Section: Determination Of Thermodynamic Parametersmentioning
confidence: 94%
“…The stability of the bound complex is determined by the differences in the noncovalent interactions between the Pc and the DNA as temperatures varied using a nonlinear least-squares algorithm. 48 At these temperatures, DNA does not undergo any structural degradation. The absorption spectra were analyzed by assuming phthalocyanine:DNA molar ratios as 1:1 and 2:1.…”
Section: Determination Of Thermodynamic Parametersmentioning
confidence: 94%
“…The stability of the bound complex is determined by the differences in the noncovalent interactions between the Pc and the DNA as temperatures varied by nonlinear least-squares algorithm. 63 At these temperatures, DNA does not undergo any structural degradation. The absorption spectra were analyzed by assuming Pc:DNA molar ratios as 1:1 and 2:1.…”
Section: Determination Of Thermodynamic Parametersmentioning
confidence: 94%
“…They found that interaction of the cationic porphyrazines was remarkably stronger than the anionic phthalocyanines [25]. Another study concerning the interaction of thymoquinone with G-quadruplex DNA was conducted by Salem et al [26]. They concluded that interaction of thymoquinone with G-quadruplex will contribute to the inhibition of telomerase enzyme and cancer's proliferation.…”
Section: Literature Surveymentioning
confidence: 99%